Scanning Electron Microscopic Study on Oviduct of jaffrabadi Buffalo during Follicular Phase - Kumar, Vishnudeo; Vyas, K N (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was conducted on oviduct of adult Jaffrabadi buffaloes during follicular phase of estrous cycle. Study revealed that the oviductal mucosa showed large number of longitudinal folds which were connected by transverse folds, lined with ciliated and non-ciliated cells. Lining epithelial of infundibulum was mainly consist of ciliated cell with few non-ciliated cells. Ampullary region in the follicular phase showed extensive ciliation similar to infundibulum. Isthmus showed less ciliated cells as compared to infundibulum and ampulla.
Keywords: Jaffrabadi buffalo; Oviduct; SEM; Follicular phase